Effectiveness and safety of first-line antiretroviral regimens in clinical practice: a multicentre cohort study. (15th July 2020) - Alejos, Belén; Suárez-García, Inés; Rava, Marta; Bautista-Hernández, Azucena; Gutierrez, Félix; Dalmau, David; Sagastagoitia, Iñigo; Rivero, Antonio; Moreno, Santiago; Jarrín, Inma; ,
Abstract: Objectives: We compared 48 week effectiveness and safety of first-line antiretroviral regimens. Methods: We analysed HIV treatment-naive adults from the Cohort of the Spanish HIV/AIDS Research Network (CoRIS) starting the most commonly used antiretroviral regimens from 2014 to 2018. We used multivariable regression models to assess the impact of initial regimen on: (i) viral suppression (VS) (viral load <50 copies/mL); (ii) change in CD4 cell count; (iii) CD4/CD8 normalization (>0.4 and >1); (iv) CD4 percentage normalization (>29%); (v) multiple T-cell marker recovery (MTMR: CD4 > 500 cells/mm 3 plus CD4 percentage >29% plus CD4/CD8 > 1); (vi) lipid, creatinine and transaminase changes; and (vii) discontinuations due to adverse events (AE). Results: Among 3945 individuals analysed, the most frequently prescribed regimens were ABC/3TC/DTG (34.0%), TAF/FTC/EVG/CBT (17.2%), TDF/FTC + DTG (11.9%), TDF/FTC/EVG/CBT (11.7%), TDF/FTC/RPV (11.5%), TDF/FTC + bDRV (8.3%) and TDF/FTC + RAL (5.3%). At 48 weeks, 89.7% of individuals achieved VS with no significant differences by initial regimen. CD4 mean increase was 257.8 (249.3; 266.2) cells/mm 3, and it was lower with TAF/FTC/EVG/CBT and TDF/FTC/RPV compared with ABC/3TC/DTG. CD4 percentage normalization was less likely with TAF/FTC/EVG/CBT, and MTMR was less likely with TAF/FTC/EVG/CBT and TDF/FTC + RAL. The proportion of discontinuations due to AE was higher with TDF/FTC + bDRV (9.7%), followed by TDF/FTC/EVG/CBT (9.5%) and TDF/FTC + DTG (7.9%). Compared with ABC/3TC/DTG, cholesterol and LDL mean increases were higher with TAF/FTC/EVG/CBT and lower with TDF/FTC + DTG, TDF/FTC/RPV and TDF/FTC + RAL. Higher mean increases in triglycerides were significantly associated with TAF/FTC/EVG/CBT. Regimens containing DTG showed higher creatinine increases. Conclusions: The significantly greater immunological response and safety of some combinations may be useful for making decisions when initiating treatment.